Предмет: Алгебра,
автор: mikki26
докажите тождество:
1) (a+b)^2-4ab=(a-b)^2
Ответы
Автор ответа:
0
(a+b)^2 = a^2 + 2ab + b^2 - формула скоращённого умножения
(a-b)^2 = a^2 -2ab +b^2 - формула скоращённого умножения
a^2 + 2ab + b^2 - 4ab = a^2 -2ab +b^2
a^2 - 2ab + b^2 = a^2 - 2ab + b^2
доказано
(a-b)^2 = a^2 -2ab +b^2 - формула скоращённого умножения
a^2 + 2ab + b^2 - 4ab = a^2 -2ab +b^2
a^2 - 2ab + b^2 = a^2 - 2ab + b^2
доказано
Похожие вопросы
Предмет: Геометрия,
автор: bogdangamer2234
Предмет: Математика,
автор: Tsjrjc
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Алгебра,
автор: DedGriboed
Предмет: История,
автор: amg001